Comment on “Chinese and Western sports philosophy and their differences” - Bing Zhang (Trans/Form/Ação)
Commented article: ZHU, Yuanjiao; DU, Rui. Chinese and Western sports philosophy and their differences. Trans/Form/Ação: Unesp journal of philosophy, Marília, v. 47, n. 5, “Eastern thought 2”, e02400188, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/15234.